Role of PASCAL and optical coherence tomography angiograpgy in the treatment of diffuse unilateral subacute neuroretinitis caused by large live motile worm - Navya Cherukuri; Bhavik Panchal; Hrishikesh Kaza; Shreyansh Doshi; Avinash Pathengay (Indian Journal of Ophthalmology, 2019)
A 46-year-old male presented with best corrected visual acuity (BCVA) of 20/125 in his right eye. Fundus showed disc edema, multiple yellow outer retinal crops, macular edema and a live motile worm in the subretinal space. Diagnosis of diffuse unilateral subacute neuroretinitis (DUSN) was made and pattern scanning laser photocoagulation (PSLP) was performed along with administration of oral albendazole, diethylcarbamazine and corticosteroids. Complete disappearance of the worm was observed at 2 weeks. At last follow up, final BCVA improved to 20/30. Herein, we report role of PSLP in the management of DUSN.